efforts to improve family resilience based on local wisdom and religion : maantaan marapulai tradition in minangkabau marriage - hendri hendri (Program Studi Magister Hukum Islam - UIN Bukittinggi, 2026)
The background for writing this article is the maantaan marapulai tradition of going to the house of anak daro in Nagari Baringin District, Tanah Datar Regency. In this tradition, the groom is delivered to the home of the bride’s family. This bride and groom may only live at home if the maantaan marapulai tradition has been carried out at the anak daro’s house, namely after the walimatul’urs is carried out. The man will be delivered by his family and friends to the woman’s house at night for three consecutive days. The community’s view of the maantaan marapulai tradition to the children’s house of this tradition is important to carry out because it indicates that a man who is accompanied by his family and friends indicates that the man is no longer single, has responsibilities as a husband. An overview of Islamic law on this tradition is that this tradition can be categorized as 'Urf al-Fasid because in Islam there is no prohibition for a husband and wife to live in the same house because it is legal to be husband and wife even though they have not been picked up.